Household stress and adolescent behaviours in urban families: the mediating roles of parent mental health and social supports. Issue 4 (25th September 2014) - Reynolds, Andrew D.; Crea, Thomas M.
Abstract: Using exploratory data analysis techniques, we propose a model of parent psychosocial well‐being that links financial strains and household stressors to adolescents' pro‐social behaviours and vulnerability through parent mental health and social supports. Parents of urban youth ( n = 781) who planned to attend a summer camp for at‐risk youth responded to questions surveying household, parent and child factors related to early adolescent development. We expected that the relationship of household stressors – including financial strain and household difficulties – with adolescent behaviours would be mediated by parent depression and anxiety. We also anticipated that parent social supports would have both direct and indirect effects (via parent mental health) on adolescents' pro‐social behaviours. Study findings are consistent with our hypotheses and the model performed similarly for both adolescent males and females. Implications for practice and policy in the context of programmes for urban youth are discussed.